PERANCANGAN SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN MAHASISWA BERPRESTASI DI POLITEKNIK NEGERI SAMARINDA - Anton Topadang; Tien Rahayu Tulili (Politeknik Negeri Samarinda, 2016)
The aim of this study was to draft a decision support system in determining the best students in Polytechnic Samarinda. The method used in determining student achievement is meotode Method Simple Additive weighting method (SAW) and Algorithms Fuzzy Multiple Attribute Decision Making (FMADM). The results of which can be obtained from the research is the design of a decision support system in the form of determination of student achievement that can be used as a reference for selecting the best performing student at the Polytechnic of Samarinda. Keywords: Decision Support System, SAW, FMADM, outstanding students.